Novel mitochondrial-targeted alkyl chains act as fungal specific inhibitors of C. neoformans - Edrich, Elizabeth S. M.; Young, Luke; Spencer, John; McGown, Andrew; Moore, Anthony L.; Gourlay, Campbell W. (Frontiers in Microbiology, 2025)
Cryptococcus neoformans is the causal agent of cryptococcal meningitis in immunocompromised patients and increasing instances of anti-fungal resistance have led to investigations into new alternative antifungal targets. For example, C. neoformans possesses an Alternative Oxidase enzyme (Aox) that has been implicated in stress resistance and virulence that may represent a viable antifungal target. Here we test the efficacy of mitochondrially-targeted Colletochlorin B, which has been shown to inhibit the Aox of Candida albicans in vitro. Two derivatives of Colletochlorin B, which we modified to improve delivery to mitochondria, were identified as putative fungal-specific inhibitors. ALTOX094 and ALTOX102 were able to inhibit Aox and cytochrome bc1in vitro and demonstrated strong inhibitory effects against C. neoformans growth and viability. Further analysis suggested that the antifungal properties of ALTOX094 and ALTOX102 were attributable to different modes of action and forms of cell death, governed largely by the alkyl chain length used to tether Colletochlorin B to the mitochondria targeting triphenylphosphine (TPP) moiety. Our findings add to the growing evidence that functionalized mitochondria targeted alkyl chains may developed further as an effective class of antifungal and are effective against C. neoformans.